Maintenance Therapy in Crohn's Disease - Hillary Steinhart (Canadian Journal of Gastroenterology)
Symptoms of active Crohn’s disease may respond to one or more of a number of classes of drug therapies. These include systemic glucocorticoids, budesonide, sulphasalazine, mesalazine (5-aminosalicylates), immunosuppressive agents and antibiotics. More recently, a chimeric mouse-human antibody to tumour necrosis factor (infliximab) has been shown to induce clinical remission and endoscopic improvement in patients with moderately active Crohn’s disease refractory to other therapies. Despite this wide range of existing therapies and the potential of emerging biological therapies, recurrent Crohn’s disease continues to be a major impediment to the fulfilment of a normal lifestyle and optimal quality of life for patients with Crohn’s disease. Many drugs known to be effective for the treatment of active disease have been tried as maintenance therapy to prevent disease relapse or recurrence following medical or surgical therapy. The available evidence suggests that most of these drugs are not as useful in maintaining remission as they are in inducing it. Systemic glucocorticoids, budesonide, mesalazine (5-aminosalicylates), sulphasalazine and antibiotics are all associated with either marginal therapeutic gain in the setting of maintenance therapy or unacceptable long term toxicity. The immunosuppressive agents azathioprine, 6-mercaptopurine and methotrexate have been shown to have a beneficial effect in maintaining remission and may be helpful as steroid-sparing agents. Repeated infusions of antitumour necrosis factor antibody maintain the improvements observed after one or two initial infusions. The relative long term safety, efficacy and cost effectiveness of the various choices of maintenance therapy remain to be determined.